Age-Related Differences in Visual Attention to Heritage Tourism: An Eye-Tracking Study - Linlin Yuan; Zihao Cao; Yongchun Mao; Mohd Hafizal Mohd Isa; Muhammad Hafeez Abdul Nasir (Journal of Eye Movement Research)
With the rising significance of visual marketing, differences in how tourists from various age groups visually engage with tourism promotional materials remain insufficiently studied. This study recruited 48 participants and used a quasi-experimental design combined with eye-tracking technology to examine visual attention, scan path patterns, and their relationship to reading performance among different age groups. Independent t-tests, correlation analyses, and Lag Sequential Analysis were conducted to compare the differences between the two groups. Results indicated that elder participants had significantly higher fixation counts and longer fixation durations in text regions than younger participants, as well as higher perceived novelty scores. A positive correlation emerged between text fixation duration and perceived novelty. Additionally, elder participants showed greater interaction between text and images, while younger participants exhibited a more linear reading pattern. This study offers empirical insights to optimize tourism promotional materials, highlighting the need for age-specific communication strategies.